Gelatinization temperature of rice explained by polymorphisms in starch synthase - Waters, Daniel L. E.; Henry, Robert J.; Reinke, Russell F.; Fitzgerald, Melissa A. (Wiley, 2006)
The cooking quality of rice is associated with the starch gelatinization temperature (GT). Rice genotypes with low GT have probably been selected for their cooking quality by humans during domestication. We now report polymorphisms in starch synthase IIa (SSIIa) that explain the variation in rice starch GT. Sequence analysis of the eight exons of SSIIa identified significant polymorphism in only exon 8. These single nucleotide polymorphisms (SNPs) were determined in 70 diverse genotypes of rice. Two SNPs could classify all 70 genotypes into either high GT or low GT types which differed in GT by 8 °C. ‘A’ rather than ‘G’ at base 2412 determined whether a methionine or valine was present at the corresponding amino acid residue in SSIIa, whilst two adjacent SNPs at bases 2543 and 2544 coded for either leucine (GC) or phenylalanine (TT). Rice varieties with high GT starch had a combination of valine and leucine at these residues. In contrast, rice varieties with low GT starch had a combination of either methionine and leucine or valine and phenylalanine at these same residues. At least two distinct polymorphisms have apparently been selected for their desirable cooking qualities in the domestication of rice.